2018
DOI: 10.1155/2018/6190254
|View full text |Cite
|
Sign up to set email alerts
|

Sheng‐Jiang Powder Ameliorates High Fat Diet Induced Nonalcoholic Fatty Liver Disease via Inhibiting Activation of Akt/mTOR/S6 Pathway in Rats

Abstract: Background and Aims Nonalcoholic fatty liver disease (NAFLD) is an alarming public health problem that directly contributes to increased prevalence of liver cirrhosis and hepatic cell cancer, but without any specific pharmacological option. Sheng-jiang powder (SJP), an empirical Chinese medicine formula to treat NAFLD, showed great efficacy but the specific mechanisms have never been reported. Therefore, we performed this study to explore the effect of SJP on NAFLD and the potential mechanism. Methods NAFLD wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…As a classic representative traditional Chinese medicine formula, Sheng-Jiang Powder (SJP) showed satisfying clinical effect in treating NAFLD with confirmed wide ranging of pharmacological effects, such as anti-inflammation, lowering body weight, mitigating insulin resistance, and regulating immune response [ 23 ]. Also, our previous study has demonstrated that SJP could effectively prevent HFD-induced weight gain and hepatic lipid accumulation and subsequent liver injury via regulating lipid metabolism-related pathways [ 24 ]. However, we have not had any knowledge about the impact of SJP on gut microbiota so far.…”
Section: Introductionmentioning
confidence: 99%
“…As a classic representative traditional Chinese medicine formula, Sheng-Jiang Powder (SJP) showed satisfying clinical effect in treating NAFLD with confirmed wide ranging of pharmacological effects, such as anti-inflammation, lowering body weight, mitigating insulin resistance, and regulating immune response [ 23 ]. Also, our previous study has demonstrated that SJP could effectively prevent HFD-induced weight gain and hepatic lipid accumulation and subsequent liver injury via regulating lipid metabolism-related pathways [ 24 ]. However, we have not had any knowledge about the impact of SJP on gut microbiota so far.…”
Section: Introductionmentioning
confidence: 99%
“…The exact pathogenesis of NAFLD is still unknown, but accumulating evidence has indicated important roles for oxidative stress, insulin resistance, endoplasmic reticulum stress, and chronic inflammation, and these factors always interact with each other and finally lead to the occurrence and development of NAFLD. Oxidative stress is often initiated by abundant production of ROS and is considered an important contributor to hepatocyte injury associated with NAFLD (Li et al 2018 ). This is in line with our findings in which significant increases in the oxidative stress markers such as MDA were accompanied by decreased activities of catalase, SOD, and GSH content in the HFD and HFD + IR groups compared to the control group, suggesting the presence of oxidative stress that may play an essential role in the insulin resistance in the HFD and HFD + IR groups.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some research demonstrated that Akt could directly inhibit the gene expression of fatty acid oxidation and thus regulate liver lipid metabolism. Although much evidence indicates that activation of the PI3K/AKT pathway is associated with marked accumulation of intracellular lipid droplets and promotion of NASH to fibrosis, some studies have revealed that PI3K/Akt activation is beneficial for ameliorating insulin resistance, oxidative stress, and lipid accumulation (Li et al 2018 ). In the current study, HFD and/or ionizing radiation exposure inhibited the activity of PI3K/Akt proteins, which in turn induced significant insulin resistance, as detected by the significant increase in the HOMA-IR index.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in obese AP rats, oxidative stress occurs locally and systemically along with the upregulation of proinflammatory cytokines and exacerbation of lipid peroxidation[10]. Our previous studies have demonstrated that high-fat diet-induced obesity can cause extensive inflammatory damage, especially multiple-organ inflammatory injury, in rats[11-13]. More importantly, obese individuals have an increased risk of developing multisystem organ failure in AP[5].…”
Section: Introductionmentioning
confidence: 99%
“…SJP has been reported to exhibit diverse biological properties, including anti-inflammatory, lipid-lowering, and immune regulatory characteristics[16]. Our previous studies have demonstrated that SJP can ameliorate the inflammatory response and histopathological lesions in multiple organs in obese rats[11-13]. In addition, a previous study reported that SJP can reduce the inflammatory response and improve the clinical symptoms and prognosis of patients with AP[17].…”
Section: Introductionmentioning
confidence: 99%